Patient-maintained propofol sedation for adult patients undergoing surgical or medical procedures: a scoping review of current evidence and technology. (January 2021) - Hewson, David W.; Hardman, Jonathan G.; Bedforth, Nigel M.
Summary: Patient-maintained propofol sedation (PMPS) is the delivery of procedural propofol sedation by target-controlled infusion with the patient exerting an element of control over their target-site propofol concentration. This scoping review aims to establish the extent and nature of current knowledge regarding PMPS from both a clinical and technological perspective, thereby identifying knowledge gaps to guide future research. We searched MEDLINE, EMBASE, and OpenGrey databases, identifying 17 clinical studies for analysis. PMPS is described in the context of healthy volunteers and in orthopaedic, general surgical, dental, and endoscopic clinical settings. All studies used modifications to existing commercially-available infusion devices to achieve prototype systems capable of PMPS. The current literature precludes rigorous generalisable conclusions regarding the safety or comparative clinical effectiveness of PMPS, however cautious acknowledgement of efficacy in specific clinical settings is appropriate. Based on the existing literature, together with new standardised outcome reporting recommendations for sedation research and frameworks designed to assess novel health technologies research, we have made recommendations for future pharmacological, clinical, behavioural, and health economic research on PMPS. We conclude that high-quality experimental clinical trials with relevant comparator groups assessing the impact of PMPS on standardised patient-orientated outcome measures are urgently required.